2017
DOI: 10.1101/107680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOT or not: examining the basis of high-occupancy target regions

Abstract: High-occupancy target (HOT) regions are the segments of the genome with unusually high number of transcription factor binding sites. These regions are observed in multiple species and thought to have biological importance due to high transcription factor occupancy. Furthermore, they coincide with house-keeping gene promoters and the associated genes are stably expressed across multiple cell types. Despite these features, HOT regions are solemnly defined using ChIP-seq experiments and shown to lack canonical mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Indeed, we found that ChIP-seq peaks that do not contain a predicted TFBS were significantly enriched at HOT/XOT regions (odds ratio = 1.43 for HOT and 1.44 for XOT, p-value < 2.2e-16, hypergeometric test, Supplementary Table S5). This observation, combined with a previous study describing that HOT/XOT regions are likely to be derived from ChIP-seq artifacts (6) , suggests that HOT/XOT regions are not derived from the direct binding of TFs.…”
Section: High-occupancy Target Regions Are Likely Not Derived From DIsupporting
confidence: 59%
“…Indeed, we found that ChIP-seq peaks that do not contain a predicted TFBS were significantly enriched at HOT/XOT regions (odds ratio = 1.43 for HOT and 1.44 for XOT, p-value < 2.2e-16, hypergeometric test, Supplementary Table S5). This observation, combined with a previous study describing that HOT/XOT regions are likely to be derived from ChIP-seq artifacts (6) , suggests that HOT/XOT regions are not derived from the direct binding of TFs.…”
Section: High-occupancy Target Regions Are Likely Not Derived From DIsupporting
confidence: 59%
“…2E). The features of ChIP-seq-specific peaks (enrichment of H3K4me3, close proximity to TSS, low CpG methylation, high expression of target genes) resembles the regions described as "hyper-ChIPable" or "phantom peaks" in yeast and in fly (Park et al 2013;Teytelman et al 2013;Jain et al 2015) and, more recently, as "HOT regions" in worm, mouse, and human ChIP-seq data (Wreczycka et al 2017). Notably, ∼51% of the mouse HOT regions overlapped with POU5F1 ChIP-seq-specific peaks, while only ∼3% of them overlapped with POU5F1 DamID-specific peaks (Fig.…”
Section: Optimization Of Damid-seq Protocolmentioning
confidence: 96%
“…(E) Expression changes of genes in D, 24 h after knockdown of Pou5f1 in ESCs (King and Klose 2017). (F ) DamID/ChIP-seq overlapping and specific peaks including mouse ChIP-seq HOT regions(Wreczycka et al 2017). 10 6 NSC SOX2 DamID-seq in comparison with ChIP-seq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We further demonstrate the ability of the bimodal network to deconvolve the sequence and prior On the other hand, some highly accessible active promoters and enhancers are bound even with weaker sequence signatures, as defined by low activation scores from the BichromSEQ sub-network in our model. We note that some TF-bound regions with high preexisting chromatin (BichromCHR) sub-network activations and low sequence (BichromSEQ) sub-network activations might represent artifactual ChIP-seq enrichment 59 .…”
Section: Discussionmentioning
confidence: 90%